1994
DOI: 10.1007/bf01412372
|View full text |Cite
|
Sign up to set email alerts
|

Cultural competency in genetic counseling

Abstract: Incorporating a cross-cultural curriculum into genetic counseling training programs demonstrates a professional conviction of genetic counselors that cultural issues are important in genetic counseling. Funded by the Special Projects Fund in 1993 from the National Society of Genetic Counselors and the Kitson Fund from the Department of Social, Organizational, and Counseling Psychology, Teachers College, Columbia University, theHandbook of Cross-Cultural Genetic Counseling was developed to provide genetic couns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Thus, a counselor's awareness of his or her own worldview, race, ethnicity, culture, language, and power status and how these variables operate in the lives of his or her self and clients is essential for multicultural counseling competence [Ota Wang, 1994]. …”
Section: Multicultural Genetic Counseling Competencementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a counselor's awareness of his or her own worldview, race, ethnicity, culture, language, and power status and how these variables operate in the lives of his or her self and clients is essential for multicultural counseling competence [Ota Wang, 1994]. …”
Section: Multicultural Genetic Counseling Competencementioning
confidence: 99%
“…Thus, clarifying one's own racial and cultural identities, developing self-acceptance, and having the ability to respectfully relate and function with people from all racial±cultural groups have become essential and necessary prerequisites for developing multicultural competence [ Johnson, 1987; Clarifying one's own racial and cultural identities, developing self-acceptance, and having the ability to respectfully relate and function with people from all racial±cultural groups have become essential and necessary prerequisites for developing multicultural competence. Pinderhughes, 1989;Carter, 1995;Ota Wang, 1994Sue et al, 1998;Cheatham, 1999;Tomlinson-Clarke and Ota Wang, 2000].…”
Section: Cross-culturalism Then To Multiculturalism Nowmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown interest in genetic testing among the deaf (Boudreault et al 2010). The differences in reasons and motivations for genetic testing among members of deaf communities indicate genetic counselling services need to consider cultural affiliation of the deaf in the provision of services (Barker 1990;Israel et al 1992;Wang 1994;Wang and Marsh 1992).…”
Section: Introductionmentioning
confidence: 99%
“…As racial and ethnic diversity increase in the United States, multicultural competence is growing in importance in genetic counseling (Coleman 1998;Lewis 2002;Wang 1994;Wang and Marsh 1992;Weil 2001). Multicultural competence involves a philosophical view that embraces inclusiveness, altruism, community-mindedness, and concern for justice (Sue 1998; Sue et al 1992).…”
Section: Introductionmentioning
confidence: 99%